MEASURING THE TECHNICAL EFFICIENCY AND THE RATE OF CHANGE IN THE TFP FOR FARMS RAIN-FED WHEAT IN THE REGION IN LIGHT OF DIFFERING SIZE AREA - & Jbara, Rijib (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study deals with the subject of measuring the impact of variation of wheat planted area categories in the region rain-fed on the technical efficiency and the rate of change in( TFPch),The basic preliminary data was obtained from field resources by relying on a stratified random sample of wheat farmers in Sulaimaniyah region including 225 farms  production during 2013-2014 season , It has been measurement of technical and Scale  efficiency in light of change and stability of the total revenue according to the production function variables using (Area ,the amount of seeds ,compound fertilizer, urea fertilizer , pesticides , machinery work , manual work ) it turns out that the average technical efficiency for the first, second ,third ,forth ,and fifth class of the cultivated areas reached around( 82% , 76% ,70%, 53%,and 72 %) respectively recording a total average of 72% for the farms included in the studied sample . The numbers of farms achieving the optimum technical efficiency were (25, 3, 11, 21 and 15) for the five categories respectively.As far as the change in the total factor productivity (TFPch)in the farms subject to the study (using the Malmquist index of productivity) the result has indicated that the change in total production stood at an average of 1.39 , and the farms in which a positive change in the total factor productivity (TFPch) was 92 farms representing 41% of the total number of the farms included in the study , a negative (TFPch) was recorded in 83 farms representing 37% of the total number of the farms included in the study .